MONEY LAUNDERING IN THE USA CRIMINAL LAW - Shashiashvili, Giorgi (European Scientific Journal, ESJ, 2012)
The article concerns one of the difficult and interesting problems of comparative criminal law – money laundering in the USA criminal law. As a result of the analysis of the existing legislation, it is ascertained that the issue of money laundering is not reflected in the USA legislation in the form of one certain law. This is conditioned by the fact that a codified mode of criminal law does not exist in this country. Besides, the analysis of the USA criminal legislation showed that money laundering is given in the legislation in the form of two models: as obtaining property by committing a crime and as generating property as a result of unlawful activities. A lot of countries, where Romano-Germanic system of law dominates, support the model of the law of money laundering. Georgia is not an exception.